1990
DOI: 10.1021/om00118a023
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-metal rhenium-platinum cluster compounds. Synthesis and characterization of three isomers of the triangular cluster complex [Re2Pt(.mu.-H)2(CO)8(PPh3)2]

Abstract: The reaction between [Re,(~-H),(CO),] and [Pt(PPh3),(C,H4)] at 273 K results in the insertion of the [Pt(PPh3),] fragment into a Re(pH)Re bond, giving the triangular cluster [RezPt(p-H)z(CO),(PPh3)2], characterized spectroscopically. On increasing the temperature, an irreversible transformation occurs, due to the exchange of one phosphine and one carbonyl between platinum and rhenium. Two other isomers are formed in this way, characterized by 'H and 31P NMR, which differ in the location of the phosphine bound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 1 publication
2
19
0
Order By: Relevance
“…2 We have now found that compound 1 is able to react in mild conditions with the ethane-like molecule [Re2(CO)ro], 3, through a completely different pathway, leading to the addition of up to three PtPPh3 fragments on [Rez(CO)lo]. The reaction, at room temperature, went to completion by bubbling N2 (to remove C2H4) through a solution of 3 and an excess of 1 (ca.…”
mentioning
confidence: 98%
“…2 We have now found that compound 1 is able to react in mild conditions with the ethane-like molecule [Re2(CO)ro], 3, through a completely different pathway, leading to the addition of up to three PtPPh3 fragments on [Rez(CO)lo]. The reaction, at room temperature, went to completion by bubbling N2 (to remove C2H4) through a solution of 3 and an excess of 1 (ca.…”
mentioning
confidence: 98%
“…It is related to a number of similar compounds that have been reported. [4] Compound 4 contains four metal atoms: two of platinum and two of rhenium. The molecular structure of 4 was established crystallographically.…”
mentioning
confidence: 99%
“…It was found that 4 adds one equivalent of H 2 (1 atm/ 25 8C) to yield the new tetrahydrido compound [Pt 2 Re 2 (CO) 7 -(PtBu 3 ) 2 (m-H) 4 ] (5) in 71 % yield. Compound 5 was also characterized crystallographically.…”
mentioning
confidence: 99%
“…The solid-state structure of (35) has been determined, 129 and in both these isomers one of the PPh 3 groups is ligated to a rhenium atom. This isomerization hence requires an exchange of a CO and phosphine ligand between the rhenium and platinum centres.…”
Section: ' 1 3 0 Have R E P O R T E D Detailed N M R Studies On [Rementioning
confidence: 99%
“…A very interesting form of isomerism is shown by the complex [Mo 2 Fe 2 (n 3 -S) 2 (CO) 8 CP 2 ] (CP = Cp or Cp 1 ) (128) and (129). 484 " 7 The two isomers differ in the metal core geometry in that (128) has a butterfly skeleton, while (129) has a planar skeleton.…”
Section: 546mentioning
confidence: 99%